SISTEM PENDUKUNG KEPUTUSAN PENYEDIA DOKUMEN DALAM PENGAJUAN SERTIFIKASI HALAL MENURUT LPPOM-MUI - Siti Ulfah Fauziah, Kudang Boro Seminar, Irman Hermadi, Nugraha Edhi Suyatma (Department of Agroindustrial Technology, Bogor Agricultural University, 2017)
Halal certification is a form of moslem consumer protection to solve halal problems. Acceleration of the submission process depends on accuration and completeness of the proposed requirements document. This research objective was to accelerate the registration process of halal certification, especially on data entry phase of materials which applied into decision support system. Decision support system can be used to determining the supporting documents of materials types. Input to the decision support system were names of materials from the products to be certified. The decision support output came from integration of decision tree analysis with J48 model and critical points of materials which resulted 43 rules. The output from this system consisted of flow process diagram, technical specifications, COA (Certificate of Analysis) or material purchase documents, halal certificate, and blank document. The decision support system had been developed into web-based system using hypertext preprocessor (PHP) programming language and MySQL (My Structured Query Language) database management system.Keywords: decision support system, decision tree halal certification, supporting document of materials, web base